ANALISIS ATTITUDE, KNOWLEDGE DAN SKILL TERHADAP KINERJA DI HOTEL ( Studi Tentang Kinerja Alumni Victoria Hotel School ) - Novita Putri Untari; Sudarwati Sudarwati; Ida Aryani Diyah Purnomo Wulan (Program Studi Manajemen Fakultas Ekonomi Universitas Samudra, 2018)
This analysis is to know the influence of attitude, knowledge and skill on the performance of Victoria Hotel School alumni at the hotel. The method in this research is quantitative method using multiple linear regression as its analysis tool. a questionnaire was given to several HRD hotels to assess the 80 alumni of Victoria Hotel School who had worked. The result of this research attitude, Knowledge and skill influence simultaneously and partially to the performance at Hotel. for the influence of variable independent attitude, Knowledge and skill have percentage equal to 51,3% while the rest 48,7% influenced by other free variable like motivation, leadership style, work environment and job satisfaction .